2017
DOI: 10.1038/pcan.2017.2
|View full text |Cite
|
Sign up to set email alerts
|

TCF7 is suppressed by the androgen receptor via microRNA-1-mediated downregulation and is involved in the development of resistance to androgen deprivation in prostate cancer

Abstract: We demonstrated that the AR-miR-1 axis negatively regulates the novel oncogenic factor, TCF7. Dysregulation of TCF7 promoted a survival advantage and resistance to androgen deprivation, suggesting its therapeutic potential for castration-resistant prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…Many TCF variants with distinct properties are produced by the alternative splicing and promoter usage [4,20], resulting in distinct and sometimes redundant functions of TCF genes. In the TCF family, the upregulation of TCF7 was observed in many types of cancers, such as prostate cancer [8], adrenocortical tumor [21], pancreatic cancer [22], renal cancer [23], and breast cancer [24]. In our study, we demonstrated that TCF7 was significantly associated with positive metastasis of GC, perhaps because TCF7 promotes the invasion-involved Wnt target gene in GC cells.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Many TCF variants with distinct properties are produced by the alternative splicing and promoter usage [4,20], resulting in distinct and sometimes redundant functions of TCF genes. In the TCF family, the upregulation of TCF7 was observed in many types of cancers, such as prostate cancer [8], adrenocortical tumor [21], pancreatic cancer [22], renal cancer [23], and breast cancer [24]. In our study, we demonstrated that TCF7 was significantly associated with positive metastasis of GC, perhaps because TCF7 promotes the invasion-involved Wnt target gene in GC cells.…”
Section: Discussionmentioning
confidence: 51%
“…As a transcriptional activator, much evidence demonstrates that overexpression of TCF7 promotes progression or correlates with poor prognosis in several types of cancers. Moreover, the downregulation of TCF7 by some miRNAs can suppress tumor progression or carcinogenesis [68]. Ectopic activation of Wnt signaling is critical in progression of gastric cancer [9], but the expression and clinical significance in gastric cancer has never been explored.…”
Section: Introductionmentioning
confidence: 99%
“…44,45 Tcf7 is one of the members of the Tcf/lef family. Abnormally expressed high Tcf7 was found in many types of cancer, such as prostate cancer 46 and renal cell carcinoma. 47 It plays an important role in cancer on Wnt signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the miR-1-2 promoter is also targeted by ‘Kruppel like factor 4’ (Klf4), which expression itself is induced by the AR [95]. Additionally, androgen-induced miR-1 downregulates TCF7 in prostate cancer cell lines and therefore negatively impacts the Wnt signaling pathway [96]. Another target gene of miR-1, in the context of the transition of PCa from androgen-sensitive to castration-resistant, is ZBTB46 [97].…”
Section: Androgen-regulated Micrornas (Andromirs)mentioning
confidence: 99%